The Importance of Parent/Child Communications About Children’s Savings Accounts for Developing a College-Bound Identity: None - Zheng, Haotian; Elliott, William; O'Brien, Megan (Advances in Social Sciences Research Journal, 2022)
Children’s Savings Accounts (CSAs) not only can help children and families to pay for expenses related to postsecondary education but also produce positive social and psychological effects, such as children’s college-bound identity. In this sense, CSAs provide a rich context for parent and child to communicate about college and ultimately for children to co-construct a college-bound identity with parents. This study examines the relationship between parent/child communication about participation in CSA and children’s college-bound identity. Using data from 506 parent/child dyads participating in the Promise Scholars CSA, we examine if parent/child communications about their CSA are associated with a stronger college-bound identity, an important predictor of future academic success. Propensity score weighting is performed to minimize the impact of selection bias. Multiple imputations are performed to handle missing data. We find evidence of higher college-bound identity scores among communicator dyads compared to non-communicator dyads and the comparison group. We also find that the difference in college-bound identity scores is not statistically significant between non-communicator dyads and the comparison group. Given this finding, CSA programs may consider interventions that may facilitate parent/child communications about their CSA as a way of encouraging children to form a college-bound identity. Further, we posit that parent/child communications about CSA are another important way for programs to understand engagement as most programs aim to increase college attendance. Until recently, CSA programs have often narrowly understood engagement as whether families make contributions or not.